ANALISIS KEBIJAKAN INSENTIF PAJAK PENGHASILAN FINAL UMKM DITANGGUNG PEMERINTAH PADA KPP PRATAMA SAWAH BESAR DUA - Nisa Oktavia; Maya Saroh; Murti Marga Astuti; Antoni Ludfi Arifin (Jurnal Widya Akuntansi dan Keuangan, 2023)
The ongoing Covid-19 pandemic has an impact on all lines of life, especially in the economic sector in Indonesia, including Micro Small Medium Enterprise (MSME) players who have also experienced a decline in sales turnover. In response to this, the government issued a policy of incentive provision in the form of Government-Borne MSME Final Income Tax as a stimulus to taxpayers affected by Covid-19. This study aims to analyze the implementation of the incentive provision policy at the Primary Tax Office of Sawah Besar Dua in 2020. A qualitative method was used in this study with a descriptive approach. Data was collected through interviews, documentation and observation. This study uses the Policy Implementation Theory of Van Meter and Van Horn. The results of the study indicate that the Government-Borne MSME Final Income Tax policy has been implemented by tax officials. This incentive program has been utilized by 25% of taxpayers. This means that the policy has not been maximized. This is due to several issues such as the lack of campaign to taxpayers so that there are still many of them who are not aware of the tax incentive policy.